Assistentialism in food aid resources. An analysis of the problematization of food insecurity through the What's the Problem Represented to Be (WPR) framework - Inza-Bartolomé, Amaia; Escajedo San Epifanio, Leire (Cuadernos de Trabajo Social, 2025)
Third sector food aid resources have responded to food insecurity situations in rich countries. A certain problematization of said insecurity has brought about certain conveniences of a secondary order, such as the profitability that the food industry achieves with the recommodification of donated food or that would otherwise be wasted, the de-responsibilization of governments with respect to the right to food, as well as the charity's own resources, which have helped public opinion see them uncritically.However, the biased view of poverty, which appears to be easy to compensate through these channels, has had harmful effects on users. The assistance-oriented nature of the aforementioned food aid resources stigmatizes and reinforces exclusion. It also offers us important information about the quality of welfare systems. The methodological framework of the WPR, through a series of questions, helps us investigate the roots of the construction of the prevailing problematization, explore the taken-for-granted truths, and offers us keys for debate, as well as for an alternative  problematization.As a main conclusion, this work suggests that it is necessary to repoliticize the link between food insecurity and aid resources, problematize food poverty in light of the right to food, avoiding stigma and taking care of inclusion pathways.
Keywords: food aidresources; food insecurity; problematization; WPR; assistentialism